Nutritional Status of Adolescents Based on Stress Levels and Energy Intake in Surakarta: Cross-Sectional Study - Tri Nawang Wulan Nurhayati; Firmansyah; Nur Lathifah Mardiyati (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Adolescents are a group that is vulnerable to nutritional problems due to various physiological and psychosocial changes. In Indonesia, the prevalence of malnutrition and overnutrition among adolescents is still relatively high. Various factors directly affect nutritional status, namely food intake, as well as indirect factors such as stress. Stress can disrupt eating behavior and affect appetite regulation, resulting in changes in energy intake and body weight. The purpose of this study was to determine the relationship between stress levels and energy intake with the nutritional status of adolescents in Surakarta. This study used an observational method with a cross-sectional approach involving 155 respondents using simple random sampling. Stress levels were measured using the Depression Anxiety Stress Scales (DASS-42) questionnaire, energy intake was assessed through a 7-day food record, and nutritional status was measured using z-scores with age-specific body mass index (BMI-for-Age). The results of the study, which were tested using Chi-Square and correlation tests, showed that there was a relationship between stress levels and nutritional status (p = 0.000; r = 0.317) and a relationship between energy intake and nutritional status (p = 0.000; r = 0.494). In conclusion, stress levels and energy intake are interrelated factors that affect the nutritional status of adolescents This study shows the need for interventions focused on stress management education and the promotion of a balanced diet to improve adolescent health.